Register Collection of Employee Reports at Secretariat Aceh Reintegration Agency - Muntasir; Salam, Abdus; Bahruni (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2022)
The aim of this research is; knowing the data collection on employee report registers at the Aceh Reintegration Agency Secretariat, and designing desktop-based data collection on employee report registers at the Aceh Reintegration Agency Secretariat. The development method used is prototyping and this application is designed using VB.NET while the evaluation process is carried out based on 4 categories, namely Content, Organization and Readability, Navigation, User Interface Design and Performance and Effectiveness. From the results of research and observations that have been carried out at the Aceh Reintegration Agency (BRA), it can be concluded that; 1) With the employee registration information system at the Aceh Reintegration Agency (BRA) it becomes precise, and accurate, especially in the personnel section, and getting information about the employee becomes easier, 2) This information system is able to overcome the problems that often occur in the Reintegration Agency Aceh (BRA) difficulties in controlling and supervising employee data and reporting which can avoid delays in making employee reports every year and for a certain period of time, and 3) Developing an information system program to obtain quality information, and 4) Based on the evaluation of the current desktop application display With the prototype design, it is known that each category has an increase in the usability value. Content, Organization and Readability previously had a value of 0.53 and increased to 0.73. The Navigation category was previously 0.42 to 0.62. The previous User Interface Design category was 0.42 to 0.64 and the previous Performance and Effectiveness category was 0.67 to 0.68.